World Bank Research Digest, Vol. 9(1) - World Bank (Washington, DC, 2014)
This research digest newsletter includes the following headings: village governments, gender, and public goods provision in Tamil Nadu; innovative health insurance in Andhra Pradesh - has it worked as planned?; a profile of private school participation in Pakistan; does involving local non-government organizations (NGOs) improve outcomes?; anatomy of a failure: an ethnography of a project in rural India; money or ideas?: constraints to entrepreneurship in rural Pakistan; and how does financial development affect firm life cycle?